CRISPR/Cas9: A powerful genome editing technique for the treatment of cancer cells with present challenges and future directions - Hazafa, Abu (Life Sci, 2020)
Cancer is one of the most leading causes of death and a major public health problem, universally. According to accumulated data, annually, approximately 8.5 million people died because of the lethality of cancer. Recently, a novel RNA domain-containing endonuclease-based genome engineering technology, namely the clustered regularly interspaced short palindromic repeat (CRISPR)-associated protein-9 (Cas9) have been proved as a powerful technique in the treatment of cancer cells due to its multifunctional properties including high specificity, accuracy, time reducing and cost-effective strategies with minimum off-target effects. The present review investigates the overview of recent studies on the newly developed genome-editing strategy, CRISPR/Cas9, as an excellent pre-clinical therapeutic option in the reduction and identification of new tumor target genes in the solid tumors. Based on accumulated data, we revealed that CRISPR/Cas9 significantly inhibited the robust tumor cell growth (breast, lung, liver, colorectal, and prostate) by targeting the oncogenes, tumor-suppressive genes, genes associated to therapies by inhibitors, genes associated to chemotherapies drug resistance, and suggested that CRISPR/Cas9 could be a potential therapeutic target in inhibiting the tumor cell growth by suppressing the cell-proliferation, metastasis, invasion and inducing the apoptosis during the treatment of malignancies in the near future. The present review also discussed the current challenges and barriers, and proposed future recommendations for a better understanding.